A method for constructing synthetic parallel tracks for augmenting in-situ data with satellite observations. (March 2020) - Pentakota, Sreenivas; Kolusu, Seshagiri Rao; Gade, Sagar V.; Srinivasu, K.; Prithvi Raj, J
Abstract: In-situ observations have significant importance for calibration and validation of satellite data, processes studies etc, however in-situ observations are often available with less spatio-temporal coverage due to practical limitations in making observations, as well as cost effectiveness. Albeit satellite observations have better spatial and temporal coverage, they have certain limitations like obstacles of cloud coverage, retrieval algorithms etc. Hence worthy inferences on the processes (that was intended to study) can be obtained only through skillful utilization of both in-situ observations, satellite and/or reanalysis products. We have illustrated a method for deriving synthetic parallel tracks to in-situ track/survey. Using this method, the satellite and/or reanalysis products can be extracted over these synthetic parallel tracks to derive worthy understanding/conclusions on the processes. The points on the original track are reproduced in terms of slope and distance, which can be utilized to construct a new synthetic parallel track initiating at a predetermined distance to the starting point of original track. As an example, we have demonstrated variations in oceanic physical properties along synthetic parallel tracks to the track of the Khai-muk cyclone. It is easy to understood using this technique that the variations in sub-surface heat content (as evidenced by variations in sea level along Khai-muk cyclone track) have a relatively major role in controlling the intensity of the system, compared to the changes in surface temperature. The method illustrated here is applicable to any geophysical track/survey with varying spatial and/or temporal extension. Highlights: A novel method for constructing synthetic parallel tracks. This method illustrated here is applicable to any geophysical track/survey with varying spatial and/or temporal extension. Tropical cyclone physical process are studied using this method.